Human newborn bacille Calmette–Guérin vaccination and risk of tuberculosis disease: a case-control study. Issue 1 (December 2016) - Fletcher, Helen; Filali-Mouhim, Ali; Nemes, Elisa; Hawkridge, Anthony; Keyser, Alana; Njikan, Samuel; Hatherill, Mark; Scriba, Thomas; Abel, Brian; Kagina, Benjamin; Veldsman, Ashley; Agudelo, Nancy; et al.
Abstract Background An incomplete understanding of the immunological mechanisms underlying protection against tuberculosis (TB) hampers the development of new vaccines against TB. We aimed to define host correlates of prospective risk of TB disease following bacille Calmette–Guérin (BCG) vaccination. Methods In this study, 5, 726 infants vaccinated with BCG at birth were enrolled. Host responses in blood collected at 10 weeks of age were compared between infants who developed pulmonary TB disease during 2 years of follow-up (cases) and those who remained healthy (controls). Results Comprehensive gene expression and cellular and soluble marker analysis failed to identify a correlate of risk. We showed that distinct host responses after BCG vaccination may be the reason: two major clusters of gene expression, with different myeloid and lymphoid activation and inflammatory patterns, were evident when all infants were examined together. Cases from each cluster demonstrated distinct patterns of gene expression, which were confirmed by cellular assays. Conclusions Distinct patterns of host responses toMycobacterium bovis BCG suggest that novel TB vaccines may also elicit distinct patterns of host responses. This diversity should be considered in future TB vaccine development.